2021
DOI: 10.3389/fimmu.2021.763086
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines Targeting Novel Cancer-Associated Antigens Frequently Expressed in Head and Neck Cancer Enhance the Efficacy of Checkpoint Inhibitor

Abstract: HPV-independent head and neck squamous cell carcinoma (HNSCC) is a common cancer globally. The overall response rate to anti-PD1 checkpoint inhibitors (CPIs) in HNSCC is ~16%. One major factor influencing the effectiveness of CPI is the level of tumor infiltrating T cells (TILs). Converting TILlow tumors to TILhigh tumors is thus critical to improve clinical outcome. Here we describe a novel DNA vaccines to facilitate the T-cell infiltration and control tumor growth. We evaluated the expression of target antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…More recently, LOH in the chromosomal 9p arm involving the loss of JAK2 and PD-L1 was shown to affect immune responses in HNC and may promote immune evasion and foster the malignant transformation of OPMD (64). Hence, intervention to induce T cell infiltration or combination therapy targeting oncogenic genes involved in immunoediting may be a feasible approach to reactivate immune responses in the non-immune reactive subtype (65).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, LOH in the chromosomal 9p arm involving the loss of JAK2 and PD-L1 was shown to affect immune responses in HNC and may promote immune evasion and foster the malignant transformation of OPMD (64). Hence, intervention to induce T cell infiltration or combination therapy targeting oncogenic genes involved in immunoediting may be a feasible approach to reactivate immune responses in the non-immune reactive subtype (65).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence encoding a secreted fusion of idiotype protein (scFv) and PVXCP was cloned into the pING vector. Vaccine construction incorporated the following components: a patient heavy chain leader peptide, VH-DH-JH fragment, linker L218 (GSTSGSGKPGSGEGSTKG) [ 16 ], light chain VL-DL-JL fragment, linker peptide AAAGPGP containing the NotI site [ 17 ], and the PVXCP sequence. The assembled plasmids were verified by restriction mapping and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research showed that a dual-antigenic peptide vaccine (PV1) derived from FJX1 and MAGED4B proteins induces antitumor immune responses in vitro ( 118 ). Increased infiltration of antigen-specific T cells into the tumor is induced by PV1, which is an important criterion for the success of immunotherapy and is associated with better patient prognosis ( 176 ). The cytotoxic cytokines, such as IFN-γ, granzyme B, and Th1, are secreted upon exposure to target cells which express the respective antigen post-PV1 stimulation and further inactivate a variety of oncogenic signaling pathways and induce the apoptosis of tumor cells ( 118 , 176 ).…”
Section: Therapeutic Strategies Targeting Spkkpsmentioning
confidence: 99%
“…Increased infiltration of antigen-specific T cells into the tumor is induced by PV1, which is an important criterion for the success of immunotherapy and is associated with better patient prognosis ( 176 ). The cytotoxic cytokines, such as IFN-γ, granzyme B, and Th1, are secreted upon exposure to target cells which express the respective antigen post-PV1 stimulation and further inactivate a variety of oncogenic signaling pathways and induce the apoptosis of tumor cells ( 118 , 176 ). PV1 inhibits tumor growth and significantly improves the prognosis when used alone or in combination with anti-PD1 ( 176 ).…”
Section: Therapeutic Strategies Targeting Spkkpsmentioning
confidence: 99%
See 1 more Smart Citation